Effect of Equivalence Ratio on EFB Pellet Gasification Characteristic using Thermal Arc Plasma Suction Downdraft Gasifier - Mohamad Zin, Muhamad Asrulhazwan; Samiran, Nor Afzanizam; Meng-Choung Chiong, Meng-Choung Chiong; Ishak, Mohammad Zulfikar; Hamid, Muhammad Suhail Sahul (semarak ilmu, 2023)
The present study investigated the performance of thermal arch plasma suction downdraft gasification which utilizing pelletized empty fruit bunch as a feedstock in producing syngas with high thermochemical conversion efficiency. Gasifying medium of air was used in this system. Syngas produced was evaluated and measured in terms of gas composition, carbon conversion efficiency, cold gas efficiency, syngas yield and calorific value. The effect of different equivalence ratio ranged from 0.18 to 0.46 was also evaluated. The results reported that syngas produced contained higher CO of 14.2 vol% at higher equivalent ratio, 0.42. In contrast to H2 content, higher composition of 9.92 vol% was produced at lower equivalent ratio, 0.18. HHV and CGE value was higher at equivalent ratio of 0.36 which correspond to the balanced constituent of CO, H2 and CH4 at this condition. CCE and syngas yield was maximum at higher equivalent ratio of 0.46 due to higher production of CO from carbon elements. The results of the present study provided a useful data and guideline of equivalent ratio range for operational of plasma downdraft reactor.